Morse Code Unlock: An Interactive Escape Room That Teaches Morse Code - Mustaza, Akmal Azhad; A Hamid, Rahayu (Applied Information Technology And Computer Science, 2026)
Morse Code Unlock is an educational desktop game that uses an escape room format to teach Morse code. Learners are becoming less interested in Morse code due to its repetitive and outdated teaching methods, despite its importance in emergency response, aviation, and military communication. To address this, the game blends education and entertainment by allowing players to decode Morse code and solve increasingly complex puzzles. Developed using the Game Development Life Cycle methodology, it boosts engagement through features such as menus, hints, visual prompts, and sound effects. Morse Code Unlock is well suited for training programs, workshops, and educational institutions, and supports both formal and informal learning. Through user testing, the game successfully met its objective of providing a positive first exposure to Morse code, making the experience accessible and enjoyable for beginners. It encourages the development of communication and problem-solving skills while reinforcing the relevance of Morse code in real world contexts.